The bletchley riddle eaudiobook - Sepetys, Ruta (Listening Library, 2024)
A stunning collaboration between award-winning and bestselling authors Ruta Sepetys and Steve Sheinkin, this middle grade historical adventure follows two siblings at Bletchley Park, the home of WWII codebreakers, as they try to unravel a mystery surrounding their mother’s disappearance. Remember, you are bound by the Official Secrets Act… Summer, 1940. Nineteen-year-old Jakob Novis and his quirky younger sister Lizzie share a love of riddles and puzzles. And now they’re living inside of one. The quarrelsome siblings find themselves amidst one of the greatest secrets of World War II—Britain’s eccentric codebreaking factory at Bletchley Park. As Jakob joins Bletchley’s top minds to crack the Nazi's Enigma cipher, fourteen-year-old Lizzie embarks on a mission to solve the mysterious disappearance of their mother. The Battle of Britain rages and Hitler’s invasion creeps closer. And at the same time, baffling messages and codes arrive on their doorstep while a menacing inspector lurks outside the gates of the Bletchley mansion. Are the messages truly for them, or are they a trap? Could the riddles of Enigma and their mother's disappearance be somehow connected? Jakob and Lizzie must find a way to work together as they race to decipher clues which unravel a shocking puzzle that presents the ultimate challenge: How long must a secret be kept?